Kaṭṭaikūttu : The Flexibility of a South Indian Theatre Tradition - Bruin, H.M. de, (Asian Studies - Book Archive pre-2000., 1999)
This book gives an insight into Kaṭṭaikkūttu, a living Tamil theatre tradition. Taking the perspective of performers as a starting point, it analyses how this theatre tradition has been able to adjust itself to changing conditions and challenges because of its inherent flexibility. The phenomenon of flexibility pervades both the formation and internal arrangements of theatre companies and the actual performances themselves. The first part of the book focuses on Kaṭṭaikkūttu in its historical and social context. It traces the theatre's disengagement from its organic embedding in the social and ritual village organization and its transition towards a more autonomous and more professional regional theatre form during the last fifty to hundred years. This transformation was accompanied by processes of professionalization and commercialization, which had their impact on the practitioners and the performances. The second part of the book provides a detailed analysis of the working of oral Kaṭṭaikkūttu texts in performance. Through a flexible handling of the oral - verbal and musical - material within the boundaries of a relatively fixed framework underlying these texts, Kaṭṭaikkūttu performers try to fulfill to the best of their abilities the demands of sponsors, audiences and occasions.